Partisipasi Mahasiswa KKN Dalam Kegiatan Sosialisasi Bahaya Narkoba dan Kekerasan Seksual di SD Dumas Surabaya - Eko Wahyudi; Leonardo Benito Maspaitella; Salsabila Ardila Wahyuningtyas; Handra Marciano Sultan Pranayoga; Chairunisa Alya Rahmawaty (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Community Service Program (KKN) are part of educational activities as well as community service which become a learning tool for students to contribute actively to society while helping to solve the problems they face. Participation is independent participation or active initiative in various activities and situations in a group or community. The participation of KKN students in the community is demonstrated in the teaching activities carried out at SD Dumas Surabaya. The Merdeka Belajar Kampus Merdeka (MBKM) held at SD Dumas Surabaya is a program designed to provide education about the dangers of sexual violence and drugs. With this implementation method, it is hoped that Dumas Elementary School students will gain a better understanding of the dangers of sexual violence and drugs, and be able to apply this knowledge in everyday life. This is important to create a safer, healthier and more prosperous environment for the entire community.